Real time algorithm for magnet's localization in capsule endoscope - Shuang Song; Chao Hu; Mao Li; Wanan Yang; Meng, M.Q.-H. (2009 IEEE International Conference on Automation and Logistics, 2009)
To track the movement of a wireless capsule, a magnetic localization and orientation system is designed. In this system, a permanent magnet is enclosed in the capsule, which generates a magnetic field around. With the magnetic sensor array arranged out of the human body, we can measure the magnet's magnetic signals, and compute the capsule's 3D localization and 2D orientation parameters by applying an appropriate algorithm. In this paper, we presented a real time localization algorithm that consists of the Levenberg-Marquardt (LM) algorithm and the Least Squares Curve Fitting Method. The experimental results show that this algorithm has good accuracy, high speed and high robustness.